2013
DOI: 10.1111/opo.12052
|View full text |Cite
|
Sign up to set email alerts
|

How does atropine exert its anti‐myopia effects?

Abstract: In the following point‐counterpoint article, internationally‐acclaimed myopia researchers were challenged to defend the two opposing sides of the topic defined by the title; their contributions, which appear in the order, Point followed by Counterpoint, were peer‐reviewed by both the editorial team and an external reviewer. Independently of the invited authors, the named member of the editorial team provided an Introduction and Summary, both of which were reviewed by the other members of the editorial team. By… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
78
0
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(88 citation statements)
references
References 18 publications
1
78
0
8
Order By: Relevance
“…Although the exact mechanism of atropine is not known, it is believed that atropine acts directly or indirectly on the retina or scleral, inhibiting thinning or stretching of the scleral, and thereby eye growth. 20,22 This eye growth possibly involves a series of biochemical steps, and atropine presumably inhibits 1 or more steps along this pathway, creating changes in the feedback mechanisms and up-or downregulating other receptors both up-and downstream. When atropine is withdrawn, it is not surprising that there may be a sudden growth spurt as the inhibitory action is released.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the exact mechanism of atropine is not known, it is believed that atropine acts directly or indirectly on the retina or scleral, inhibiting thinning or stretching of the scleral, and thereby eye growth. 20,22 This eye growth possibly involves a series of biochemical steps, and atropine presumably inhibits 1 or more steps along this pathway, creating changes in the feedback mechanisms and up-or downregulating other receptors both up-and downstream. When atropine is withdrawn, it is not surprising that there may be a sudden growth spurt as the inhibitory action is released.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the effects, particularly of higher doses of atropine, may be more complex than we think, possibly causing change or modification of the mechanism regulating eye growth at different anatomic and biochemical levels. 20,22 It is uncertain whether these changes could be permanent (e.g., resulting in sustained acceleration of myopia even years after stopping atropine), the system will reset itself, or we can modulate subsequent eye growth (e.g., by tapering atropine more slowly over time). Somewhat reassuring is the finding that the proportion of children who progressed >0.5 D in the washout year (i.e., requiring retreatment) decreased with increasing age in all 3 treatment arms (Fig 2).…”
Section: Discussionmentioning
confidence: 99%
“…To date, it is uncertain how atropine acts to retard progression of myopia and axial elongation, likely the cause of myopia. 18 Initially, atropine was used based on the putative role of excessive accommodation in causing myopia. Subsequent studies have shown that atropine also inhibits myopia in animals (eg, chickens) that have no accommodative facility.…”
Section: Discussionmentioning
confidence: 99%
“…The cM 4 genomic clone was obtained as previously described, 18 and the M 4 (MAR0400000) and hADRA2A (AR0A2A0000) receptor clones were purchased from the cDNA Resource Center (Bloomsburg University Foundation, Bloomsburg, PA, USA result of activity at transfected, and not endogenous, receptors. 45,46 Stable CRISPR M 3 -knockout LX293T cells are referred to as CR-M 3 cells.…”
Section: Dna and Expression Vectorsmentioning
confidence: 99%
“…18 For example, most mAChR antagonists, even very potent ones such as 3-quinuclidinyl benzilate (QNB) or dicyclomine, do not inhibit myopia in chicks, and those muscarinic antagonists that do so inhibit myopia require concentrations that can be orders of magnitude above their inhibition constants for blocking mAChRs (Table 1). 16,19 Furthermore, ablating ‡90% of choline acetyltransferase (ChAT)-containing amacrine cells-the only known source of retinal acetylcholine (ACh; the natural agonist at mAChRs)-in the chick has no effect on the eyes' ability to achieve emmetropia, nor does elimination of retinal ChAT impair myopia inhibition by atropine.…”
mentioning
confidence: 99%